From a Molar to a Molecular Approach to the Developmental Trajectory of Syntax Comprehension of Persons with Intellectual Disability. Issue 1 (22nd November 2021) - Facon, Bruno; Magis, David; Knutsen, Dominique
Abstract: The aim of our study was to investigate whether the developmental trajectories of syntax comprehension of participants with or without intellectual disability are comparable. We obtained results from a syntax comprehension test of 615 typically developing participants (mean chronological age = 4.61 years, SD = 0.85) and 615 participants with intellectual disability (mean chronological age = 12.22 years, SD = 3.14) matched on a nonverbal cognitive measure. We examined these results by applying several statistical approaches to the overall scores for the syntax test and then to the scores for each of its 92 items. Results showed negligible between‐group differences in developmental trajectories, at both levels of analysis (overall and item scores). This lack of effect suggests that the relationship between cognitive development and syntax comprehension is comparable for the two groups of participants. Theoretical and practical implications of these findings are discussed. Abstract :